EFECTO DE DISTINTOS TIPOS DE ENVASE, SUSTRATO y GRADOS DE ENDURECIMIENTO EN LA PRODUCCIÓN DE PLANTA DE QUERCUS SUBER L. y QUERCUS ROTUNDIFOLIA LAM. - SUÁREZ, Ma ANGELES; ÁZQUEZ, FRANCISCO V; Baselga, Pilar (II Congreso Forestal Español, 1997)
Different treatments about olm oak (Quercus rotundifolia Lam.) and cork oak (Quercus suber L.) plants' production are comparied. It has been worked with two kinds of containers, three kinds of substratums and two degrees of plants' protection during the cultivation
Keywords: Cork oak; Nursery; Olm oak; Plant's production; Quercus